2021
DOI: 10.1186/s13048-021-00911-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on factors associated with ovarian cancer: an umbrella review of systematic review and meta-analyses

Abstract: Following cervical and uterine cancer, ovarian cancer (OC) has the third rank in gynecologic cancers. It often remains non-diagnosed until it spreads throughout the pelvis and abdomen. Identification of the most effective risk factors can help take prevention measures concerning OC. Therefore, the presented review aims to summarize the available studies on OC risk factors. A comprehensive systematic literature search was performed to identify all published systematic reviews and meta-analysis on associated fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…OvCa is a multifactorial disease, including demographic, reproductive, gynecologic, hormonal, genetic, and lifestyle factors ( Tanha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OvCa is a multifactorial disease, including demographic, reproductive, gynecologic, hormonal, genetic, and lifestyle factors ( Tanha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among other factors, such as hereditary, environmental, and lifestyle factors, inflammation is an important risk factor for OvCa. Several studies have suggested that factors related to ovarian surface epithelium (OSE) inflammation, such as ovulation, endometriosis, and pelvic inflammatory diseases (PIDs), are associated with an increased risk of OvCa ( Trabert et al, 2020 , Tanha et al, 2021 ). Mucin 16 (MUC16) is a membrane-associated gene that encodes cancer antigen 125 (CA125), and the upregulation of its expression is another mechanism underlying the effects of inflammatory factors in OvCa ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity may increase the risk of EC by a variety of mechanisms, including the conversion of androgens to estrogens via the aromatase activity [ 10 ]. OC is also associated with hormonal factors, such as nulliparity, early-onset menarche, late-onset menopause, and the use of hormonal treatments [ 4 , 11 ]. Other factors that interact with sex hormones could potentially modify the risk of EC and OC.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also a well-established risk factor for breast cancer (BC) [ 11 ] and ovarian cancer (OC) [ 12 ], which are among the most commonly diagnosed tumors in women worldwide, and a leading cause of cancer mortality [ 13 , 14 , 15 , 16 ]. Although epidemiologic data have associated obesity with increased risk of cancer development and progression for a variety of tumors long ago, only recently the underlying molecular mechanisms have begun to be characterized [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%